Developments in risk-based decision making: Responding to the threat of Rift Valley fever (RVF) and other trans-boundary diseases - Jost, Christine; Minjauw, B.; Mariner, Jeffrey C.; Bett, Bernard K.; Clark, A. (2012)
Following the 2006-2007 outbreak of RVF in East Africa, the International Livestock Research Institute (ILRI), UN-FAO and US-Centers for Disease Control and Prevention organized a series of meeting for decision-makers to discuss how responses to the outbreak could have been conducted in a more timely and effective manner. Participants observed that the ‘all or nothing’ approach used in the decision to declare the emergency and mobilize responses did not contribute to the successful mitigation of the outbreak. Stakeholders concluded that a phased approach to decision-making utilizing incremental responses to the escalating risk of an outbreak could be more effective. They built a decision framework based on a matrix of events paired with action categories. The events served as decision points, and the action categories suggested responses at each point. Initially, the framework was named a decision support tool, but the RVF Risk-Based Decision Framework (RVF-RBDF) is now recognized as a more accurate name for this innovation. The RBDF enjoyed interest and decision-makers used the framework to mobilize actions to the RVF alarm of 2008. The framework is not prescriptive and easily incorporates technical enhancements such as new generation risk maps or more efficient vaccination strategies. In 2011, representatives of the Horn of Africa and the Middle East reviewed the RVF-RBDF at a meeting held in Dubai and hosted by ILRI and the African Union Interafrican Bureau for Animal Resources. The meeting recommended that the RVF-RBDF be developed as a framework for management of RVF risk in inter-regional trade. The meeting noted that the RVF-RBDF was a new paradigm for animal health management that merited application to other health issues as well. Plans are underway to apply the framework process in the regional context of North Africa using the lessons of the 2011 RVF outbreak in Mauritania.